Implementation of academy information database security using the blowfish method on the Medicom Campus - Jonas Franky Rudianto Panggabean; Leliana Harahap; Sartika Dewi Purba; Sutrisno Situmorang; Kamson Sirait (Jurnal Mantik, 2023)
Data is an authentic fact or evidence which must be stored and kept secure in order to avoid unwanted disturbances or threats. To avoid threats from parties who abuse or are not responsible, there are many ways to secure data, one way to do this is to create an encryption method. Methods of data security can be seen from the confidentiality of data against a threat that can be used with the blowfish algorithm. Blowfish is a 64-bit block chipper with variable key length. This algorithm can encrypt data in text form. This encryption produces ciphertext that is easy to understand and understand. Ciphertext is changing the form of text into codes that are difficult to understand and can be returned to their original position if using the same key when the data is encrypted. Data encryption techniques in databases are one of the steps used to secure and maintain data confidentiality. With this database encryption, code can be generated so that people who do not have access rights cannot access the database because the key has been generated. Database is a storage place for collections of data and information. The entire academy information system is stored in the database. Therefore, to maintain the security of the academy information database on the Medicom campus, cryptography with the Blowfish algorithm is needed. In this regard, the authors are very interested in carrying out an implementation of a document data / information security with cryptographic techniques using the Blowfish and Base64 algorithm methods. This algorithm technique was chosen because modern cryptography is a symmetric key in the form of a block cipher. This built Blowfish algorithm can encrypt text in text form. Encryption is done using a certain key, resulting in ciphertext.